Determinants of China's Private Consumption : An International Perspective - Guo, Kai (IMF Working Papers; Working Paper ;, 2010)
This paper gauges the key determinants of China's private consumption in relation to GDP using data on the Chinese economy and evidence from other countries' experiences. The results suggest there is nothing "special" about consumption in China. Rather, the challenge is to explain why the conditioning variables-notably a low level of service sector employment, the level of financial sector development, and low real interest rates-are so different in China relative to other countries' historical experience. The results suggest, in particular, that efforts to further raise household income and the share of employment in the services sector, as well as to develop capital markets, including liberalizing interest rates and creating alternative savings instruments are likely to have the biggest impact on consumption. Other mechanisms to raise household income and mitigate household-specific risk (such as by improving the healthcare and pension systems) also have a role to play.